Nabhi's compendium of orders under central government health scheme (CGHS) - Edited by Garg, Ajay Kumar (New Delhi Nabhi Publications, 2023)
The speciality of this book is that it has been written in a simple and lucid language and the relevant orders have been referred to at all appropriate places. Text of the relevant orders has been annexed to the relevant chapters for easy reference. Besides Index of Office Memoranda, Letters etc. referred in the book have been provided to enhance the practical utility of the book. It includes List of Empanelled Hospitals/ Diagnostic Centres, Package Rates for Treatments/ Tests, Recognised Cancer Hospitals with Rates, List of AYUSH Hospitals with Rates and List of CGHS Wellness Centres.
Keywords: Orders Under Central Government Health Scheme CGHS